DETECTION OF THE PRESENCE AND CONCENTRATION OF HEAVY METALS IN SELECTED RIVERS IN THE PROVINCE OF SAMAR - Bañares, Adam Christopher B.; Alvarez, Ma. Lourdes C. (International Journal of Research -GRANTHAALAYAH, 2015)
Heavy metals has been one of the feared toxins today because of its psychological and physiological effect. This research was designed to determine the heavy metals present in Calbayog and Antiao River and to obtain the concentration of the present heavy metals. This study was conducted based on instrumental analysis which has been accepted in determining the presence and concentration of heavy metals. The environmental parameters were determined first. pH of Antiao and Calbayog River is 7.53 and 7.23, respectively, thus they are slightly basic. Salinity of Antiao and Calbayog is 30 ppt and 34 ppt respectively, which are high. Turbidity of Antiao River and Calbayog are 0.94 m and 0.81 m, respectively, therefore they are quite turbid. Samples are tested for the presence of heavy metal, Mercury (Hg) is present in the two rivers. Cadmium (Cd) is present in the sediment of Antiao River. Concentrations of Cd and Hg was analyzed using AAS, the concentration of the two are below detection limit. The results implied that the levels of heavy metals found in selected rivers are low, though this does not mean that the threat of these metals is absent. Bioaccumulation in living organisms could pose a greater threat.